The level of knowledge on smoking on the progression of disease in patients with chronic obstructive pulmonary disease. Preliminary results - Malinowska-Lipień, Iwona; Starzec, Grażyna; Gabryś, Teresa; Brzostek, Tomasz; Kawalec, Ewa; Reczek, Agata; Gawor, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Background. Chronic obstructive pulmonary disease (COPD) is a frequent disease: around 2 million Poles suffer of the COPD. The disease usually begins at the age of 30 and can continue for several decades. Development of the COPD is mainly caused by an active smoking, passive exposure to tobacco smoke and also certain occupational exposition on harmful smokes, dusts, gases, air pollution, as well as the infection of the respiratory system in childhood and such other factors as: a deficient of the a-1 antitripsine and the development disorder of lungs during the embryonic life period. Aim. The aim of the paper was to evaluate: - the level of COPD-affected patients’ knowledge on the subject of harmfulness of smoking and the latter’s influence on the development of the disease; - patients’ attempt to quit the addiction. Material and methods. The study employed a questionnaire consisting of two parts and containing 37 questions. The first part contained socioeconomic questions characterizing the examined group of COPD-diagnosed patients, while the second part included questions relating to the length of duration of the disease, occurrence of individual risk factors, the respondents’ smoking record, their sources and level of knowledge concerning COPD. The survey comprised a group of 30 patients (4 women and 26 men) hospitalized as a result of an aggravation of the COPD. Results and conclusions. Only one of the respondents had never smoked. The remaining respondents, i.e. 97%, were smokers at the moment of COPD diagnosis. At present, approximately 3/4 of the surveyed COPD-diagnosed patients have ceased smoking. The primary factor which induced them to abandon the habit was the diagnosis of the Chronic Obstructive Pulmonary Disease. However, despite disease exacerbation 23% of the respondents still smoke. The analysis of the survey indicates that nearly 2/3 of the respondents possess knowledge with regard to the significance of smoking in the development and the course of COPD. Moreover, the majority of the surveyed population, i.e. 94%, is aware of the addictive impact of nicotine. All the patients realize the harm caused by smoking in respiratory, cardiovascular and alimentary system. The conducted study demonstrated that the majority of the respondents possessed correct information concerning the effects of smoking on the development and the course of COPD. For the majority of the smokers, the diagnosis of COPD entailed discontinuance of the smoking addiction. However, almost every fourth of the respondents smoke in spite of the diagnosis of the COPD.